Gender Issues in Entrepreneurial Development in Benue State (Nigeria) and Counceling Implications - E.G. Egbe-Okpende; M.M. Orhungur (University of Sofia, 2012)
This paper investigates the impact of counselling on gender issues in entrepreneurial development in Benue State (Nigeria). Feminine or women constitute about 50 % of the population in Nigeria, and they make up 45% of the 70% unemployed population. In Benue State, there is low industrial and entrepreneurial skills development, so poverty and under-employment of the feminine gender is endemic. Hence, gender issues as relates to "the forgotten 50% of the world's population" or as the forgotten factor in economic development was studied using a random sample of fifty working class women. The study examines how this problem can be addressed through counselling. The descriptive survey design was used with one main research question guiding the study. The data was analysed using percentages. The re-sults of the study revealed that forty (80%) of the respondents with entrepreneurship development were influenced through education and counseling. Change in attitude of women as a result of education and their role in national development was investigated, and recommendations made on how to help women to fulfil their role by bridging the gender gap.